Generic key and catalogue of Mymaridae (Hymenoptera) of Mexico - Guzmán-Larralde, Adriana J.; Huber, John T.; Martínez, Humberto Quiroz (Zootaxa, 2017)
The Mexican genera of Mymaridae (Hymenoptera: Chalcidoidea) are keyed in English and Spanish, and a catalogue of species occurring in Mexico is presented. Thirty-six genera, including 79 named species in 20 of the genera, are reported. These are mentioned in about 100 publications either as original species descriptions or as publications that specifically mention species and/or specimens from Mexico. In the catalogue, species distributions by state are given based on literature records, and collection data are compiled from about 3630 specimens examined in eight collections in Canada, Mexico and USA. Host are listed for specimens reared mainly in Mexico. A few extralimital host records are also given.